Impact Sanitation, Childbearing Age, Number of Children, Mother's Age with the Risk of Stunting in Children - Najib, Najib; Giyarsih, Sri Rum; Listyaningsih, Umi; Nawawi, Nawawi (Jurnal Kesehatan Masyarakat, 2024)
Sanitation, childbearing age, number of children, and mother's age adequate is still the main challenge that has an impact on increasing the risk of stunting. This study aims to identify factors that affect the risk of stunting in children in Semarang City, Central Java Province, Indonesia, with a special focus on sanitation, childbearing age, number of children, and mother's age. The study used a linear regression research design with a sample of 383 mothers and their children in 2022. Data analysis was carried out using the ANOVA technique to evaluate the influence of independent variables on stunting risk. The results showed that sanitation (B = 1,060, p 0.001), age of delivery (B = 0.149, p = 0.018), and number of children (B = 1,027, p 0.001) had a significant positive relationship with stunting risk. In contrast, maternal age (B = -0.511, p 0.001) showed a significant negative association with stunting risk. These findings have important implications for the development of public health policies and practices, particularly in improving sanitation and nutritional interventions in young mothers and families with many children. This study makes a unique contribution by identifying specific variables that affect stunting risk in Indonesia, which can be used to develop more effective prevention strategies.